Compared to conventional PET/CT scanners, silicon-photomultiplier-based PET/CT scanners show higher arterial 18F-FDG uptake in whole-body 18F-FDG-PET/CT. Issue 12 (December 2021) - Kaneko, Koichiro; Baba, Shingo; Isoda, Takuro; Ishioka, Hisakazu
Abstract : Objectives: To clarify differences in arterial 18 F-FDG (fluorodeoxyglucose) uptake between silicon photomultiplier (SiPM)-based and conventional PET/CT scanners, and to compare clinical and phantom results. Patients and methods: Twenty-six patients with lung tumours underwent serial SiPM-based and conventional PET/CT scans on the same day. We compared the target-to-background ratios [TBRsi (SiPM), TBRc (conventional)] and the percentage difference between TBRsi and TBRc (ΔTBR) in the carotid artery, aorta and peripheral arteries. The correlation between ΔTBR and vessel size was also investigated. In the carotid artery, active segment analyses were performed with the threshold (TBR ≥1.6), and we compared each scanner's ratio of active segments and TBR values. We compared the clinical results with the recovery coefficients (RCs). Results: The TBRsi was significantly higher than the TBRc in the carotid artery, aorta and peripheral arteries (1.63 ± 0.22 vs. 1.43 ± 0.22, 1.65 ± 0.19 vs. 1.53 ± 0.15 and 1.37 ± 0.31 vs. 1.11 ± 0.27, mean ± SD, P  ⩽ 0.0001 for all), and the peripheral arteries showed the highest ΔTBR (24.4 ± 16.8%). The small (10–15 mm) vessels (26.9 ± 15.9%) showed significantly higher ΔTBRs than the larger vessels (7.3 ± 8.5% for 15–20 mm, 8.0 ± 12.8% for ≥20 mm, P  < 0.0001 for both). The carotid artery showed significantly higher ratios of active segment (54.5 vs. 20.5%, P  < 0.0001) and TBR values (1.85 ± 0.25 vs. 1.76 ± 0.15, P  = 0.0006) for TBRsi vs. TBRc. The differences in RCs were similar to those of ΔTBR for each vessel size. Conclusions: SiPM-based PET/CT scanners showed higher arterial 18 F-FDG uptake (especially in vessels <15 mm) than conventional scanners, and the threshold TBR ≥1.6 is not applicable for the carotid artery for SiPM-based PET/CT systems.